KEDARURATAN ENDODONSIA - Dwi Kartika Apriyono (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2010)
Emergency case in endodontic treatments need accuracy diagnostic and treatment immediately because it produces pain and puffines. We can get accuracy diagnostic by dental record, subjective inspection, objective inspection, periodontium inspection, and radiography inspection. Treatment for endodontic emergency case based on diagnostic result and etiology to reduce pain and desease in serious condition. The dentist ought to has enough knowledge and skill about pain mechanisme, patient management, diagnostic, anaesthetic, terapeutic treatment, the accuracy treatment for soft and hard tissue and can reduce anxiousness patient.